REAKSI PASAR MODAL AKIBAT PENGUMUMAN PENCABUTAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) (Studi Kasus Pada Saham IDX30 di Bursa Efek Indonesia) - Wimbardi, Ida Bagus Yoga; Negara Sudirman, I Made Surya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024, 2024)
The lifting of PPKM (Implementation of Restrictions on Community Activities) is a policy by the Indonesian government to combat Covid-19 which potentially contains information that could influence stock prices. This study aims to analyze market reactions by examining whether there are abnormal returns on the announcement of the lifting of PPKM on December 30, 2022, with a focus on IDX30 issuers during the period from August 2022 to February 2023. The method used is an event study with an event window period of 11 days, consisting of 5 days before (pre-event), the event date, and 5 days after (post-event) the announcement. To calculate the expected return, the market model is used, and the hypothesis is tested with a one-sample t-test. The results show that significant abnormal returns only occur in the period -3, while the other periods did not show any significant abnormal returns . The results of this research indicate that the announcement of the lifting of PPKM is not strong enough to influence the market, which shows the condition of the capital market in the form of semi-strong efficiency.